A Cocatalyst that Stabilizes a Hydride Intermediate during Photocatalytic Hydrogen Evolution over a Rhodium‐Doped TiO2 Nanosheet. Issue 29 (19th June 2018) - Ida, Shintaro; Sato, Kenta; Nagata, Tetsuya; Hagiwara, Hidehisa; Watanabe, Motonori; Kim, Namhoon; Shiota, Yoshihito; Koinuma, Michio; Takenaka, Sakae; Sakai, Takaaki; Ertekin, Elif; Ishihara, Tatsumi
Abstract: The hydrogen evolution reaction using semiconductor photocatalysts has been significantly improved by cocatalyst loading. However, there are still many speculations regarding the actual role of the cocatalyst. Now a photocatalytic hydrogen evolution reaction pathway is reported on a cocatalyst site using TiO2 nanosheets doped with Rh at Ti sites as one‐atom cocatalysts. A hydride species adsorbed on the one‐atom Rh dopant cocatalyst site was confirmed experimentally as the intermediate state for hydrogen evolution, which was consistent with the results of density functional theory (DFT) calculations. In this system, the role of the cocatalyst in photocatalytic hydrogen evolution is related to the withdrawal of photo‐excited electrons and stabilization of the hydride intermediate species; the presence of oxygen vacancies induced by Rh facilitate the withdrawal of electrons and stabilization of the hydride. Abstract : A hydride species is generated on the Rh site in the Rh‐doped titana nanosheet as an intermediate species for the evolution of hydrogen molecules. This was confirmed by both experimental and computational methods. The oxygen vacancy in the first coordination shell of the RhOx unit contributes to the formation of the Rh−H (hydride) species, and the hydride is formed at the vacancy site.